2018
DOI: 10.4236/psych.2018.94050
|View full text |Cite
|
Sign up to set email alerts
|

A Study on Maximization Paradox and Its Psychological Origin

Abstract: Compared with satisficers, maximizers intend to pursue optimal results, leading to more negative emotions and worse experience. Even when they do get a better result, they are still less satisfied. We call it "maximization paradox". Theoretically, the purpose of this study is to enrich and deepen research in fields of the maximization paradox and its psychological origin. What's more, we intend to provide feasible advice for corporations and the government on the basis of our findings. By reviewing existing li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 44 publications
0
1
0
Order By: Relevance
“…Maximizers also tend to be dissatisfied with their choices, as other studies have found [ 13 ]. Compared with satisficers, maximizers intend to pursue optimal results, leading to more negative emotions and worse experiences [ 14 ].…”
Section: Hypothesesmentioning
confidence: 99%
“…Maximizers also tend to be dissatisfied with their choices, as other studies have found [ 13 ]. Compared with satisficers, maximizers intend to pursue optimal results, leading to more negative emotions and worse experiences [ 14 ].…”
Section: Hypothesesmentioning
confidence: 99%